2022
DOI: 10.29228/jamp.52793
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Relationship between Health Literacy and Attitudes towards COVID-19 Vaccine in Adult Individuals

Abstract: Although it is known that the level of health literacy is effective in determining the direction of individuals' attitudes towards their own health, its effect on the attitudes towards COVID-19 vaccine is not yet known exactly. The aim of this study is to determine the relationship between health literacy and attitudes towards COVID-19 vaccine in adult individuals. This study is a cross-sectional design. The study was conducted with literate individuals aged 18 or over (N=210), in Turkey. The data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…On the contrary, functional skills may have been challenged by complex terminologies and technical information provided by the media, which may explain the lower functional score, also among highly educated individuals. 28,34,35,47,50,53,55,57,59,[61][62][63] In this review, the highest scores for both functional and interactive-critical scales were found in patients who completed a university degree, supporting that a higher level of education is positively associated with a higher level of VL. 53,59,61 This is comparable with studies showing that education is the most determinant factor of HL and those who have a higher level of education have a higher level of COVID-19 VL.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…On the contrary, functional skills may have been challenged by complex terminologies and technical information provided by the media, which may explain the lower functional score, also among highly educated individuals. 28,34,35,47,50,53,55,57,59,[61][62][63] In this review, the highest scores for both functional and interactive-critical scales were found in patients who completed a university degree, supporting that a higher level of education is positively associated with a higher level of VL. 53,59,61 This is comparable with studies showing that education is the most determinant factor of HL and those who have a higher level of education have a higher level of COVID-19 VL.…”
Section: Discussionmentioning
confidence: 58%
“…The majority of studies found that HL is a significant factor in COVID-19 vaccine acceptance. 28 , 47 , 50 , 52 , 53 , 55 57 , 59 The research also showed that HL is a predictor of vaccine hesitancy, and low HL skills might result in vaccine hesitancy when people find inadequate and inaccurate information about the COVID-19 vaccines on the internet. 29 , 47 The study in Turkey reported that the association between vaccine hesitancy and health system mistrust was mediated by HL.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations